Immune inhibitory ligand CD200 induction by TLRs and NLRs limits macrophage activation to protect the host from meningococcal septicemia. - Mukhopadhyay, S; Plüddemann, A; Hoe, J; Williams, K; Varin, A; Makepeace, K; Aknin, M; Bowdish, D; Smale, S; Barclay, N; Gordon, S (2010)
Macrophage activation is essential for protection against bacterial pathogens but needs to be regulated to prevent damage to the host. We show a key role for the immune inhibitory receptor CD200R and its ligand CD200 in the context of infection with the Gram-negative human pathogen Neisseria meningitidis. N. meningitidis induced CD200 but downregulated CD200R on macrophages in a manner dependent on Neisserial lipopolysaccharide, Toll-like receptor-4 (TLR-4), and the MyD88 pathway but independent of a known Neisserial receptor, scavenger receptor A (SR-A). Agonists of the pattern-recognition receptors nucleotide oligomerization domain 2 (NOD2) and NACHT-LRR protein 3 (NALP3) also induced CD200. The NF-κB member c-Rel was essential for TLR-, NOD2-, and NALP3-mediated induction of CD200. CD200(-/-) animals showed higher lethality in response to experimental meningococcal septicemia, induced higher levels of proinflammatory cytokines, and recruited increased numbers of activated leukocytes, despite comparable bacterial clearance. Thus CD200 is induced by TLR-, NOD2-, and NALP3-mediated pathways, limiting their function and protecting the host from excessive inflammation.